Clinical presentation, treatment, and outcome of parathyroid carcinoma: results of the NEKAR Retrospective International Multicenter Study - Lenschow, Christina; Schrägle, Sina; Kircher, Stefan; Lorenz, Kerstin; Machens, Andreas; Dralle, Henning; Riss, Philipp; Scheuba, Christian; Pfestroff, Andreas; Spitzweg, Christine; Zielke, Andreas; Nießen, Anna; et al. (Annals of surgery, 2022)
Objective: - In this retrospective cohort study, we describe the clinical presentation and workup of parathyroid carcinoma (PC) and determine its clinical prognostic parameters. Primary outcome was recurrence free survival. - Summary Background Data: - PC is an orphan malignancy for which diagnostic workup and treatment is not established. - Methods: - Eighty-three patients were diagnosed with PC between 1986 and 2018. Disease-specific and recurrence-free survivals were estimated with the Kaplan-Meier method. Risk factors for recurrence were identified by binary logistic regression with adjustment for age and sex. Thirty-nine tumors underwent central histopathological review. - Results: - Renal (39.8%), gastrointestinal (24.1%), bone (22.9%), and psychiatric (19.3%) symptoms were the most common symptoms. Surgical treatment was heterogeneous [parathyroidectomy [PTx)] alone: 22.9%; PTx and hemithyroidectomy: 24.1%; en bloc resection 15.7%; others 37.3%] and complications of surgery were frequent (recurrent laryngeal nerve palsy 25.3%; hypoparathyroidism 6%). Recurrence of PC was observed in 32 of 83 cases. In univariate analysis, rate of recurrence was reduced when extended initial surgery had been performed (P = 0.04). In multivariate analysis low T status [odds ratio (OR) = 2.65, 95% confidence interval (CI) 1.02-6.88, P = 0.045], N0 stage at initial diagnosis (OR = 6.32, 95% CI 1.33-30.01, P = 0.02), Ki-67 <10% (OR = 14.07, 95% CI 2.09-94.9, P = 0.007), and postoperative biochemical remission (OR = 0.023, 95% CI 0.001-0.52, P = 0.018) were beneficial prognostic parameters for recurrence-free survival. - Conclusion: - Despite a favorable overall prognosis, PC shows high rates of recurrence leading to repeated surgery and postoperative recurrent laryngeal nerve palsy and hypoparathyroidism. In view of the reduced recurrence rate in cases of extended surgery, ipsilateral completion surgery may be considered when PC is confirmed.
Gesehen am 19.04.2022